Atomic resolution defocused electron ptychography at low dose with a fast, direct electron detector - Song, J; Allen, C; Gao, S; Huang, C; Sawada, H; Pan, X; Warner, J; Wang, P; Kirkland, A (Springer Nature, 2019)
Electron ptychography has recently attracted considerable interest for high resolution phase-sensitive imaging. However, to date studies have been mainly limited to radiation resistant samples as the electron dose required to record a ptychographic dataset is too high for use with beam-sensitive materials. Here we report defocused electron ptychography using a fast, direct-counting detector to reconstruct the transmission function, which is in turn related to the electrostatic potential of a two-dimensional material at atomic resolution under various low dose conditions.